Ragam Jenis, dan Bentuk Surat di Dunia Pendidikan - Darmansah, Tengku; Syahbanda Nst, M Rezi; Margolang, Ade Irvan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Correspondence is an important form of written communication in the world of education. The variety, form, and type of letters used in educational contexts are very diverse, reflecting the various communication needs and goals between the parties involved, including students, teachers, parents, and administrative parties. Official educational letters usually include notification letters, permission letters, invitation letters, certificates and decision letters. Each type of letter has a specific format and structure according to its purpose and function. For example, notification letters are often used to convey important information such as changes to school schedules or activities, while permission letters are used by students or parents to request permission to be absent. Invitation letters are generally used to invite parents or external parties to school events. Apart from that, certificates and decision letters are used to provide official statements or decisions related to academic and administrative processes. A good understanding of the types, forms and types of letters is very important for all parties in the world of education so that communication can run effectively and efficiently. In this research the author used a qualitative method with a library research approach. Library research is research that functions to obtain information from books, magazines, documents, historical records or in other words the facilities contained in the library.